The Role of inhabitant requirement in reforming the housing interface Sulaimani city as a case study - Kani M. Muhammed (Sulaimani Journal for Engineering Sciences, 2019)
Arcitecture is civilizied edifice , it have actions and reactions , already it places with historical distance . And housing as one of the architectural phenomena has been affected since ancient times and still changes in all levels of dimensions of life in terms of social and economic changes, intellectual and political , These changes affected the dwelling and the process of producing the external form. One of the most important variables that we observe in our daily lives is the change in the shape of the housing elevations , Requirements and needs of the resident . so the research aims to finding the design indicators to forming the housing elevations which compatible with alteration of resident requirment from the connection with housing characteristcs which consider as one of the aims of house designing , it describe as the main scale for selecting house Performance efficiency . Through this research we can highlight the essence of resident requirements and Study the concept of architecture form of house elevation , Identify design characteristics and its components , The study examined the human requirements within the residential environment and its classification, studying the functional requirements and needs of the housing elevations, obtaining data and analyzing them, and then finding the indicators for changing the elevations according to the changing requirements by studying the correlation between the physical value of the dwelling, The theoretical foundations of applying these variables to a group of samples selected by the study community using the graphical analysis form, obtaining the data and tabulating them in special tables and reaching conclusions for the final recommendations.